THE USE OF KWL-PLUS ON IMPROVING READING COMPREHENSION OF THE TENTH GRADE STUDENTS OF SMA NEGERI 2 BANJAR - Detri Suryantini Made (Journal on Studies in English Language Teaching (JOSELT), 2021)
This study aimed at improving the students’ achievement in reading comprehension through the use of K-W-L Plus strategy. The study was designed in the form of an action-based research. It was conducted in two cycles consisting of three sessions in which two sessions were for treatments and one session was for test. Each cycle involved four steps, namely: planning, action, observation and reflection. The subjects of the study were 34 students. The data were obtained by using tests (pre-test, post-test I and post-test II), researcher’s diary, and questionnaire. The results indicated that the students’ reading comprehension improved along with the implementation of K-W-L Plus strategy. It can be seen from the improvement of the students’ mean score from pre-test (45.89), post-test I (65.63), to post-test II (75.00). The improvement also can be seen from the result of the questionnaires in which it indicated that the students gave positive response toward the application of K-W-L Plus Strategy. Based on the result of the study, it can be concluded that the implementation of K-W-L Plus Strategy can improve reading comprehension of the tenth-grade students of SMA Negeri 2 Banjar especially class X IPS 3.